Prilaku Konsumen Digital Dalam Memilih Pembayaran Belanja Online Pakai PAYLATER - Marlis Chafri (PT. AHLAL PUBLISHER NUSANTARA, 2026)
With the rapid development of online lending in the era of digitalization, PayLater platforms have emerged as financial products that are closely connected to consumers. Carrying the service motto “buy now, pay later,” PayLater allows consumers to conduct transactions (purchasing goods or services) without making immediate payments, with settlement carried out later—either in the following month or through installments—based on agreed tenors and interest rates. This mechanism differs from conventional online loans, which directly disburse cash to users’ bank accounts. PayLater services are generally integrated into e-commerce applications (such as Shopee PayLater and Akulaku) or travel platforms (such as Traveloka PayLater), and are now also offered by banks (including BCA PayLater and Livin’ PayLater). These services provide varying limits, interest rates, and tenors, and are regulated by the Financial Services Authority (OJK) to ensure consumer protection and transaction security. Through PayLater, shopping transactions are considered safer from misuse or fraud by merchants or producers, as payments will be refunded to the consumer’s PayLater balance if purchased goods are not delivered. PayLater users are predominantly from the Millennial and Generation Z cohorts. Keywords: digital consumer behavior, PayLater, literature study, payment decision Abstrak Dengan adanya perkembangan pinjaman Online di era digitalisasi platform Paylater hadir menawarkan prodak yang sangat dekat dengan konsumen dengan moto layanan